Improved eDNA assay evidences further refugia for critically endangered smalltooth sawfish (Pristis pectinata) in Mexico - Bonfil, Ramón; Díaz-Jaimes, Píndaro; Palacios-Barreto, Paola; Mendoza Vargas, Oscar Uriel; Ricaño-Soriano, Melina (Frontiers in Marine Science, 2024)
Sawfishes are considered one of the most threatened marine fish taxa globally, with major contractions in their geographic range documented over the last 50 years across all oceans. Two sawfish species used to be found in Mexico, but a historical lack of research and first-hand baseline information recently raised concerns about the fate of both species there. Recent Local Ecological Knowledge (LEK) and environmental DNA (eDNA) research has shown that: a) Pristis pectinata and P. pristis were formerly abundant and widely distributed in the Mexican Atlantic coast, and the latter also in the Mexican Pacific coast, and b) sawfishes (at least P. pectinata) are still found in some coastal refugia in central Veracruz state and Campeche state on the Atlantic coast. In the present research we developed improved primers that allow for better species ID resolution for Pristis pectinata and P. pristis through successful sequencing of eDNA samples by amplifying a 270 bp fragment of the CO1 gene. Our results based on the analysis of 305 eDNA samples showed an improved positive species identification rate through sequencing, demonstrate that P. pectinata occurs in other coastal refugia along the Yucatán Peninsula in the Mexican Caribbean, and suggests this species might be extirpated from southern Veracruz, while no P. pristis eDNA has been found along the Atlantic coast.